Prevalence of Antibiotic Resistant E.Coli and Salmonella from Retail Poultry Meat across Mumbai. - Sonavane, A.; Meera Sankarankutty, K. (International Journal of Engineering and Technology, 2018)
Salmonellosis and Escherichia coli infection is a major public health concern both in developed and developing countries. The use of antimicrobial therapy is the main mode of treatment for infections caused by E.coli and Salmonella spp . The majority of these infections are associated with the consumption of products such as poultry, meat, water, vegetables, eggs, milk, seafood, and fresh produce contaminated with Salmonella and E.coli. The objective of this study was to check the prevalence of antibiotic resistant E.coli and Salmonella spp from freshly cut raw poultry meat and to know the antimicrobial sensitivity pattern of these isolates to common antibiotics. Total number of 50 retail poultry meat  samples was studied from different locations across Mumbai. All samples were randomly selected from each ward and all the samples were found to be contaminated with E. coli and Salmonella spp. Out of 50 samples all of them showed the presence of E.coli and salmonella .103 E.coli isolates and 282 Salmonella isolates were identified. The E. coli and Salmonella isolates were found to be resistant to multiple antibiotics including Ampicillin, Gentamicin, Vancomycin, Tobramycin, Streptomycin, Ciprofloxacin and Ceftriaxone. Using the CLSI 2015 breakpoints for disc diffusion, 0.97% (1/103) E.coli isolates and 1.42% (4/282) Salmonella isolates were  intermediately resistant to Ceftriaxone and the remaining isolates were resistant to all the other  antibiotics used in the study. This study highlights the urgent need for surveillance and check on the rapid spread of antibiotic resistance via the food borne pathogen route to the human population.
Keywords: antibiotic resistance; E.coli; raw poultry; Salmonella.